The changing transmission of uncertainty shocks in the US: An empirical analysis - Haroon Mumtaz; Konstantinos Theodoridis (Queen Mary University of London, School of Economics and Finance, 2014)
This paper investigates if the impact of uncertainty shocks on the US economy has changed over time. To this end, we develop an extended Factor Augmented VAR model that simultaneously allows the estimation of a measure of uncertainty and its time-varying impact on a range of variables. We find that the impact of uncertainty shocks on real activity and financial variables has declined systematically over time. In contrast, the response of inflation and the short-term interest rate to this shock has remained fairly stable. Simulations from a non-linear DSGE model suggest that these empirical results are consistent with an increase in the monetary authorities' anti-inflation stance and a 'flattening' of the Phillips curve.
Keywords: C15; C32; E32; 330; FAVAR; Stochastic volatility; Uncertainty shocks; DSGE model